Exploring "˜Moana's Achieved Identity': A movie analysis of the main character - Tlonaen, Zuvyati Aryani (LITERA, 2023)
Research on identity status in literary works has not been in-depth exploration. Those researches discussed the identity status in general and were still very limited in literary study. Therefore, this study explores one of the identity statuses in detail using Kroger's (2005) achieved identity characteristics consisting of three domains; the personality variable, cognitive process and interpersonal relationship. Each domain has achieved identity features. This research is a documentary. The procedures were reading the script repeatedly; identifying the main character's actions, thoughts, reflections, thoughts, feelings, and desires; coding, classifying, analyzing and interpreting the data. The results indicated that Moana's personality, cognitive process, and interpersonal relationships proved that Moana's achieved identity in the three domains is well built. She has most of the features of achieved identity. This study also proved that identity status can be explored in fictional characters. Therefore, future research can explore this identity or other identity statuses in depth. Parents or schools can use movies with characters with this identity to help children develop their identity status to the highest, achieved identity.Keywords: Achieved identity,identity status, movie